Inequalities in health care in the Northeast region: An analysis considering the different stages of life - Moreira Aristides dos Santos, Anderson; Brasil Araújo, Arthur; Madeira Triaca , Lívia (Revista Brasileira de Estudos Regionais e Urbanos, 2025)
This paper aims to analyse inequalities in access to health care in the Northeast region compared to Brazil, considering the distinct stages of an individual’s life. The analysis is based on data from the 2013 and 2019 National Health Survey. The major results reveal a pro-rich inequality across all the age groups examined in the Northeast region. Although this inequality is less pronounced than the national average, it exhibited an increasing trend across all age groups, except for children, whose inequality index showed a decreasing trend. The older adults group exhibited the lowest rate of inequality. Regarding the associated socioeconomic factors, health insurance emerged as a significant explanatory variable, accounting for a considerable proportion of these inequalities across all cases. The Family Health Strategy reduces pro-rich inequality for all age groups, especially the older adults. Health needs factors have shown to contribute more to older individuals (adults and older adults). Therefore, there is a compelling need to implement or enhance more targeted and effective public policies that can address regional and socioeconomic specificities with greater robustness.